Gambaran Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja RSI Ibnu Sina Simpang Empat Tahun 2023 - Mailan Azima; Meri Herliza; Dessy Angraini (Yayasan Literasi Sains Indonesia, 2024)
Hospitals are workplaces that have a large workforce with a high risk of occupational disease or work accidents. Based on interviews conducted at RSI Ibnu Sina Simpang Empat and data reports, there were 6 cases of work accidents in 2022. The research aims to find out an overview of the implementation of the occupational safety and health management system at Ibnu Sina Simpang Empat Islamic Hospital in 2023. The research design uses qualitative methods with descriptive approach. The informants in this research were the K3RS committee, nurses and human resources. The research was carried out by means of in-depth interviews, observation and document review. The research results show that the K3 policy has been issued by the hospital director and K3 experts have been consulted. K3RS planning involves identifying the environment in the field and taking considerations. The implementation of the K3RS plan is guided by Minister of Health Regulation No. 52 of 2018. Monitoring and evaluation of K3RS performance is carried out by the K3RS team once every three months. Reviewing and improving K3RS performance is an evaluation carried out twice a year. It is recommended to hospital management that educational delivery is not only verbal but also in writing and on sheets regarding the delivery of the applicable laws.